Evaluation of the Effect of Phytocomplex on Chondroprotective Biomarkers in an Experimental Model of Osteoarthritis in Rats - Shridhar PANDYA; Chetan SAVALIYA; Dheeraj NAGORE; Vaishali UNDALE; Shubhada KHADE; Nishant MANTE (Modern Medicine)
Osteoarthritis (OA) is most prevalent joint disease and major contributor to non-fatal burden in India, with prevalence rates of 22% - 39%. The use of conventional medication can be associated with insufficient clinical management and serious side effects. The present study aims to evaluate the anti-arthritic activity and chondrocytes protection and regeneration potential of Joint Support Product (JSP) in monosodium Iodoacetate induced Osteoarthritis rat model. Pain threshold, knee joint swelling, Blood inflammatory parameters like Tissue necrosis factor, Interlukin-6, Leukotriene B 4, C- reactive protein and arthritic biomarkers Matrix metalloproteinase-13 and Cartilage Oligomeric Matrix Protein, were estimated. Also Radiographic and histopathological evaluation were done to estimate the severity of OA. Treatment of JSP demonstrated significant increase in pain threshold by 68 % and decrease in knee joint swelling by 92 %. The inflammatory markers decreased significantly (p< .00001) after treatment with JSP. The Tissue necrosis factor decreased by 55 %, Interlukin-6 by 61%, Leukotriene B 4 by 57%, C- reactive protein by 69 % and arthritic biomarkers - Matrix metalloproteinase by 88% and Cartilage Oligomeric Matrix Protein by 37% as compared to disease control rats. Also the radiological evaluation and gross histopathology of rats showed improved chondrocytes structure. Thus JSP’s analgesic, anti-inflammatory, chondrocyte regeneration, and chondroprotective properties have therefore demonstrated an anti-arthritic impact.